Sensitive Direct Converting X‐Ray Detectors Utilizing Crystalline CsPbBr3 Perovskite Films Fabricated via Scalable Melt Processing. Issue 4 (20th January 2020) - Matt, Gebhard J.; Levchuk, Ievgen; Knüttel, Judith; Dallmann, Johannes; Osvet, Andres; Sytnyk, Mykhailo; Tang, Xiaofeng; Elia, Jack; Hock, Rainer; Heiss, Wolfgang; Brabec, Christoph J.
Abstract: Here the fabrication of an inorganic metal‐halide perovskite CsPbBr3 based X‐ray detector is reported utilizing a simple, scalable, and cost‐sensitive melt processing directly on substrate of any size. X‐ray diffraction analysis on the several 100 mm thick melt processed films confirms crystalline domains in the cm 2 range. The CsPbBr3 film features a resistance of 8.5 GΩ cm and a hole mobility of 18 cm 2 V −1 s −1 . An X‐ray to current conversion rate of 1450 µC Gyair −1 cm −2 at an electric field of 1.2 × 10 4 V cm −1 and a detection limit in the sub µ Gyair s −1 regime is demonstrated. The high crystallinity and chemical purity of the melt processed CsPbBr3 films are suggested to be responsible for a performance which is on par to current state‐of‐the‐art Cd(Zn)Te based X‐ray detector technology. Abstract : Highly crystalline metal‐halide CsPbBr3 perovskite films are fabricated via melting directly on a substrate. As direct application an X‐ray sensing device with a sensitivity on par to the current state‐of‐the‐art CdTe detector technology is demonstrated.